Instantaneous peak 2.1 W-level hybrid energy harvesting from human motions for self-charging battery-powered electronics. (March 2021) - Li, Zhongjie; Luo, Jun; Xie, Shaorong; Xin, Liming; Guo, Hengyu; Pu, Huayan; Yin, Peilun; Xu, Zhibing; Zhang, Dong; Peng, Yan; Yang, Zhengbao; Naguib, Hani
Abstract: In this article, we report a wearable millimeter-size energy generator that yields instantaneous power of 2.1 W level from kinetic energy of human running motions. The generator, with a hybridization of piezoelectric and electromagnetic transductions, integrates mainly two major novel techniques: impact induced frequency up conversion effect for the piezoelectric generation and abrupt magnetic flux density change for the electromagnetic generation. The generator proves to be able to effectively harness energy from human motions, producing a power density over one order of magnitude higher than that of state-of-the-art work. This result is further validated by the charging performance, i.e. high charging rate and voltage into mF-level capacitors. Moreover, this wearable generator demonstrates the capability to charge a Li-on battery in dozens of minutes. This work can be of much significance for the development of self-charging battery powered wearable electronic devices. Graphical Abstract: ga1 Highlights: Novel hybridization of high-performance piezo stack and electromagnetic generators. Adopting abrupt magnetic flux density change in the electromagnetic generator. Matched impedance of piezo generator lowered to 100 Ω by frequency conversion effect. Total instantaneous power reaching 2.1 W of a millimeter-size configuration. Achieving fast charging towards a 180mAh Li-on battery based on running motions.